No causal genetic relationships between atrial fibrillation and vascular dementia: A bidirectional Mendelian randomization study - Gao, Ya-fang; Jin, Tian-yu; Chen, Yan; Ding, Ya-hui (Frontiers in Cardiovascular Medicine, 2023)
Background: Numerous observational studies have suggested that atrial fibrillation (AF) was associated with an increased risk of vascular dementia (VaD). However, the causal genetic relationship between AF and VaD remains unclear. To evaluate the effect of AF on VaD, we performed the Mendelian randomization (MR) analysis to investigate the causal association between AF and VaD. Methods: The Bidirectional MR analysis was conducted to explore the causal association. We applied a series of quality assessments to select significantly and independently single nucleotide polymorphisms (SNPs) from publicly available large-scale genome-wide association studies (GWAS) databases. Three methods [Inverse variance weighted method (IVW), MR-Egger method, and weighted median (WM) method] were used to derive MR estimates. In order to ensure reliable MR results, sensitivity analyses were performed to evaluate the horizontal pleiotropy and heterogeneity. Results: Our MR analyses revealed no significant genetic association between AF and the risk of VaD (IVW: OR= 1.10, 95%CI= 0.95 - 1.28, P= 0.20). In the reverse direction analysis, there was no evidence to support a significant genetic association of VaD with AF risk (IVW: OR= 1.00, 95% CI= 0.99 - 1.01, P= 0.52). Consistent results were obtained using different MR methods. Sensitivity analyses suggested no significant horizontal pleiotropy and heterogeneity in the study. Conclusion: This MR analysis did not provide evidence to support the causal association between AF on VaD risk and the causal effect of VaD on AF risk.